2013
DOI: 10.1177/0894439312473421
|View full text |Cite
|
Sign up to set email alerts
|

Elderly Persons and Internet Use

Abstract: The inclusion of the elderly in the digital era could positively impact their social and economic welfare. However, their level of Internet use is relatively low in Spain compared to other sectors of the population. The present study aims to explain the Internet use in this segment, capturing the heterogeneity across gender in the technology acceptance model (TAM). A sample of 492 individuals over 50 years old has been analyzed using the multigroup approach of structural equations models. The results show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 61 publications
2
38
0
2
Order By: Relevance
“…In addition, digitally excluded mature consumers might be disadvantaged because they are unable to access Internet application services, such as mobile health and social networking services. Therefore, governments in many developed nations have taken measures to ensure that mature consumers and other digitally excluded people have access to an Internet connection, but Internet access alone cannot deliver benefits if mature consumers have negative opinions about the Internet (Ramón-Jerónimo et al, 2013). In addition, Wagner et al (2010) found that consumers aged over 45 have different perceptions from the younger population because of the physical and cognitive changes that result from aging.…”
Section: Mature Consumers and The Internetmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, digitally excluded mature consumers might be disadvantaged because they are unable to access Internet application services, such as mobile health and social networking services. Therefore, governments in many developed nations have taken measures to ensure that mature consumers and other digitally excluded people have access to an Internet connection, but Internet access alone cannot deliver benefits if mature consumers have negative opinions about the Internet (Ramón-Jerónimo et al, 2013). In addition, Wagner et al (2010) found that consumers aged over 45 have different perceptions from the younger population because of the physical and cognitive changes that result from aging.…”
Section: Mature Consumers and The Internetmentioning
confidence: 98%
“…This has occurred at the same time as the rapid diffusion of the Internet (Ramón-Jerónimo, Peral-Peral, & Arenas-Gaitán, 2013). With the confluence of these two trends, consumers in the age group older than 40 years can enjoy benefits such as communication with their family and friends, information about health, opportunities for lifelong learning, and a variety of leisure activities (Wagner, Hassanein, & Head, 2010).…”
mentioning
confidence: 98%
“…Furthermore, Ramón‐Jerónimo et al . () argue that it is a problem that will only increase due to increased life expectancies at a time of increased speed of technological development. The discussion of technology speed is one highlighted by Ratliffe et al .…”
Section: Barriers To Engagement With Ictmentioning
confidence: 94%
“…Choudrie et al (2013) believe that the skills shortage, coupled with the speed of technology development, is the main reason why older people are being left behind by younger generations in Internet and ICT use, an issue that Phipps discussed in 2000 and yet is still as large a barrier. Furthermore, Ramón-Jerónimo et al (2013) argue that it is a problem that will only increase due to increased life expectancies at a time of increased speed of technological development. The discussion of technology speed is one highlighted by Ratliffe et al (2012), who feel that government initiatives tend to focus on the newest technologies, whereas their studies with people with disabilities show that working with older technology is perhaps more relevant to the equipment owned by the target groups.…”
Section: Barriers To Engagement With Ictmentioning
confidence: 99%
“…Previous studies have determined common demographic factors that may impact the digital lifestyles of the elderly, including age,10 education, gender, ethnicity and socioeconomic situation. However, several contradictory results have been highlighted, like gender and race 1215. Moreover, the impact of factors that affect elderly’s Internet usage may vary by age group among the elderly.…”
Section: Introductionmentioning
confidence: 99%